Le Rouge et le noir - Stendhal 1783-1842; Crouzet, Michel 1928 (Paris Garnier-Flammarion, 1964)
'Le Rouge et le Noir' is a historical psychological novel in two volumes by Stendhal, published in 1830. It chronicles the attempts of a provincial young man to rise socially beyond his modest upbringing through a combination of talent, hard work, deception, and hypocrisy. He ultimately allows his passions to betray him.The novel's full title, Le Rouge et le Noir: Chronique du XIXe siècle, indicates its twofold literary purpose as both a psychological portrait of the romantic protagonist, Julien Sorel, and an analytic, sociological satire of the French social order under the Bourbon Restoration (1814–30).
Marie-Henri Beyle (1783-1842), better known by his pen name Stendhal was a 19th-century French writer. He is highly regarded for the acute analysis of his characters' psychology and considered one of the early and foremost practitioners of realism. A self-proclaimed egotist, he coined the same characteristic in his characters' "Beylism".
Keywords: 19th Century (1801-1900); Novel; France